2020
DOI: 10.6004/jadpro.2020.11.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Pancreatitis Associated With Checkpoint Inhibitors

Abstract: Pancreatitis is a rare immune-related adverse event (irAE) associated with the use of immune checkpoint inhibitors (ICIs). It is more often associated with combined immunotherapy than by any single agent. Early signs of pancreatitis may only include elevation of lipase and amylase. Additional symptoms associated with pancreatitis include symptoms such as severe epigastric abdominal pain (that may radiate to the back, chest, or flank), nausea and/or vomiting, or dyspnea, and may indicate more advanced disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…Although it was not our primary purpose for this study, we identified numerous factors associated with ACU for the population. Some factors associated with the development of irAEs requiring hospitalizations, such as type of ICI agents, 56 platelet count, 57 pre-existing lung, cardiovascular, 56 nutritional, 56 , 58 hyperchloremia, 59 , 60 and infection conditions, 61 are documented in the literature. Variation in red blood cell size and volume is, to our knowledge, not elucidated before and significantly contributes to the accuracy of our XGBT algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not our primary purpose for this study, we identified numerous factors associated with ACU for the population. Some factors associated with the development of irAEs requiring hospitalizations, such as type of ICI agents, 56 platelet count, 57 pre-existing lung, cardiovascular, 56 nutritional, 56 , 58 hyperchloremia, 59 , 60 and infection conditions, 61 are documented in the literature. Variation in red blood cell size and volume is, to our knowledge, not elucidated before and significantly contributes to the accuracy of our XGBT algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…The development of immune-mediated diabetes is estimated at 1% with elevated lipase and/or amylase levels being common with concurrent pancreatitis 13. A related but rare adverse effect that may present with type I diabetes is ICI-associated pancreatitis with a 1% incidence based on clinical trial data and 0.3%–3.9% based on studies,14 15 although it is likely more prevalent. There have also been several cases in the literature where patients developed type I diabetes with pancreatitis from immune checkpoint blockade 3 15 16.…”
Section: Discussionmentioning
confidence: 99%
“…Z léků nově zaváděných do klinické praxe jsou popsané kazuistiky akutní pankreatitídy po check-point inhibitorech (imunoterapie v onkologii), inhibitorů proteáz (antiretrovirová léčba), tocilizumabu (monoklonální protilátka IL-6 receptoru v léčbě revmatoidní artritídy, nespecifických střevních zánětů nebo COVID 19 pneumonie) (20,21,22).…”
Section: Rizikové Lékyunclassified